Highly nonlinear optic nucleic acid thin-solid film to generate short pulse laser - Ghasemi, Marjan; Debnath, Pulak Chandra; Kim, Byungjoo; Pournoury, Marzieh; Khazaeinezhad, Reza; Hosseinzadeh Kassani, Sahar; Yeom, Dong Il; Oh, Kyunghwan (Scientific Reports, 2023)
Using aqueous precursors, we report successfully fabricating thin-solid films of two nucleic acids, ribonucleic acid (RNA) and deoxyribonucleic acid (DNA). We investigated the potential of these films deposited on a fiber optic platform as all-fiber integrated saturable absorbers (SAs) for ultrafast nonlinear optics. RNA-SA performances were comparable to those of DNA-SA in terms of its nonlinear transmission, modulation depth, and saturation intensity. Upon insertion of these devices into an Erbium-doped fiber ring-laser cavity, both RNA and DNA SAs enabled efficient passive Q-switching operation. RNA-SA application further facilitated robust mode-locking and generated a transform-limited soliton pulse, exhibiting a pulse duration of 633 femtoseconds. A detailed analysis of these pulsed laser characteristics compared RNA and DNA fiber optic SAs with other nonlinear optic materials. The findings of this research establish the feasibility of utilizing RNA as a saturable absorber in ultrafast laser systems with an equal or higher potential as DNA, which presents novel possibilities for the nonlinear photonic applications of nucleic acid thin solid films.
Keywords: DNA; Lasers; Motion Pictures; Nucleic Acids; RNA